BIBLICAL ALLUSION IN NICK VUJICIC’S TESTIMONY “MAN WITHOUT LIMBS: LIFE WITHOUT LIMITS”: AN INTERTEXTUAL ANALYSIS - Timotius Lukito Santoso (Universitas Stikubank (UNISBANK) Semarang, 2010)
The study attempts to investigate Nick Vujicic’s testimonial monologue (www.lifewithoutlimbs,org) on the basis of Fairclough (1992)’s Discourse and Social Change on Intertextuality to find out the modes and strategies of intertextuality. The study reveals that three modes of intertextuality are employed, namely sequential intertextuality (41.38%), embedded intertextuality (5.18%), and mixed intertextuality (53.44%), implying that the text was a self-reflection. With respect to the strategies of intertextuality, five strategies are employed, namely discourse representation (43.12%), presupposition (27.58%), negation (12.06%), metadiscourse (6.89%), and irony (10.35%), implying that Vujicic wanted to form his own discourse. Finally two types of biblical allusion are adopted, namely direct allusions (5.17%), indirect allusions (48.27); the rest (46.56%) is self-reflection, implying that Vujicic’s text was proselytizing in nature. Meanwhile, the pedagogical implication is that intertextuality is indispensible in writing or public speaking. Key Words : Allusion, Testimony, Intertextuality, Proselytizing